Constructivism Approach: Changes in Orientation of Indonesia in the North Natuna Sea to China's Claims - Herry Wahyudi; Luerdi Luerdi (Universitas Muhammadiyah Yogyakarta, 2021)
This article discusses Indonesia’s orientation in the North Natuna Sea in the constructivism. The article aims to look at the change of Indonesia's orientation towards the positioning of North Natuna waters following China’s claims as the part of its territories. Indonesia’s orientation used to be for economic development activities. However, Indonesia then swifted such orientation to defense and security. The article applied the constructivist theory of Alexander Went. The article applied the qualitative approach whose data collection was through literature study.